2021
DOI: 10.3390/ijerph18041937
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent and Longitudinal Relationships between Positive Youth Development Attributes and Adolescent Internet Addiction Symptoms in Chinese Mainland High School Students

Abstract: In view of growing adolescent Internet addiction (IA) in the global context, there is a great need to understand the predictors of IA and design related evidence-based intervention and prevention programs. This longitudinal study investigated the relationships between Positive Youth Development (PYD) attributes and IA problems and the mediating role of life satisfaction using a large sample of Chinese high school students (N = 2648). Separated by one academic year, students completed a questionnaire evaluating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 111 publications
(178 reference statements)
10
19
0
Order By: Relevance
“…As expected, PYD as an indicator of eudaimonic well-being, Martela and Sheldon [32] showed significant and negative impacts on the three factors of psychological distress in our samples. This finding can be supported by existing studies that have demonstrated that good PYD can relieve individuals' psychological distress (e.g., [44,45,75,76]). PYD is able to nurture youth mental health and encourage young people to make positive changes in multiple domains of their life to prevent behavioral and emotional problems [77].…”
Section: Discussionsupporting
confidence: 69%
“…As expected, PYD as an indicator of eudaimonic well-being, Martela and Sheldon [32] showed significant and negative impacts on the three factors of psychological distress in our samples. This finding can be supported by existing studies that have demonstrated that good PYD can relieve individuals' psychological distress (e.g., [44,45,75,76]). PYD is able to nurture youth mental health and encourage young people to make positive changes in multiple domains of their life to prevent behavioral and emotional problems [77].…”
Section: Discussionsupporting
confidence: 69%
“…Nevertheless, it can be argued that IA, depression, and delinquency are complex developmental disorders shaped by multiple ecological factors and causal pathways. For example, these developmental problems may be affected by individual (e.g., positive youth development attributes) and contextual factors (e.g., parenting and family functioning) simultaneously ( Shek et al, 2018b ; Zhou et al, 2020 ; Zhu and Shek, 2021a , b ; Dou and Shek, 2021 ), which may lead to the associations among IA, depression, and delinquency. In this case, effective prevention and intervention youth programs may need to focus more on promoting adolescents’ competence and skills in a holistic manner instead of only targeting at eliminating one specific disorder, including IA ( Shek et al, 2018a , 2020 ; Chung et al, 2019 ; Shek, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, with the adoption of a cross-sectional design, the causal relationships between meaning profile and political participation cannot be firmly established. According to the positive youth development perspective, it is theoretically reasonable that one’s developmental assets, including meaning in life, serve as an antecedent of adolescents’ well-being and behavioral functioning [ 65 , 66 , 67 , 68 ]. Nevertheless, to understand the direction of relationships, longitudinal designs are needed (see [ 69 ]) or an experimental design that manipulates one’s meaning in life (see [ 70 ]).…”
Section: Discussionmentioning
confidence: 99%